Analisis Komparasi Kinerja Keuangan pada PT. Bank Negara Indonesia (Persero) Tbk dan PT. Panin Bank Periode 2014-2018 - Pongoh, Greyti S. Y.; Areros, William A.; Mangindaan, Joanne V. (Sam Ratulangi University, 2019)
In measuring the soundness of the bank, Bank Indonesia uses the financial ratio of the CAMELS model (Bank Indonesia Regulation No. 6/10 / PBI / 2004) concerning the Commercial Bank Soundness Rating System. The purpose of this research is to find out the significant differences in financial performance between PT. BNI, Tbk with PaninBank and the dominant variable as a differentiator of significant financial performance between PT. BNI, Tbk with PaninBank. The data analysis method used in this study is two different tests independent sample. The results showed that of the 5 variables, there were only two variables that were not statistically different, namely Capital Adequacy Ratio (CAR) (X1) and Loan to Deposit Ratio (LDR) (X5) while the different variables were Return On Risked Asset (RORA) ( X2), Net Profit Margin (NPM) (X3) and Return On Assets (ROA) (X4)